Model Persamaan Simultan Untuk Jumlah Uang Beredar Tingkat Inflasi Dan Suku Bunga Domestik Di Indonesia - Suripto Suripto; Abdul Hakim (Optimum: Jurnal Ekonomi dan Pembangunan, 2012)
The main purpose of this study was to analyze the influence of the money supply and the rate of inflation to domestic interest rate (SBI) in Indonesia in 1998.2 - 2008.1. The approach in this study using simultanenous equation model and estimated with Two Stage Least Square (2-SLS). The results prove: First the model estimates the amount of money supply showed that gross domestic product significantly with the positive direction on the money supply, the exchange rate is not significant to the money supply and lending rates significantly negative effect on the money supply. Second The model estimates is significant and positive effect on the inflation rate, the exchange rate is not significant to the level of and time deposit rates significantly positive effect on the rate of inflation. Third, the model estimates the domestic interest rate (SBI) shows that inflation is not significant to be SBI, the money supply is not significant to the SBI, the SBI rate significantly positive